1996
DOI: 10.1007/bf01849546
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity during and after pregnancy

Abstract: The factors related to sexual behavior during pregnancy and after childbirth were studied in 352 Nigerian women. Sexual frequency was higher during the postnatal period (1.7 times per week) compared to the pregnancy period (1.5 times per week). Coital frequency also showed no difference for the various social class and age groups but was more prevalent among the primigravidas compared to the higher parity groups (p < 0.05). Vulval itching was experienced in 246 (69.9%) women although this had no effect on sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
4
19
0
2
Order By: Relevance
“…Perhaps, pregnancy, by lowering vaginal pH, prohibits the growth of Gardnerella vaginalis known to thrive in alkaline medium. 11,12 Observations from our previous report on pregnancy sexuality 2 17 This study has shown that the prevalence of Gardnerella vaginalis was lower at term gestational age (12.0%) compared with pre-term (18.2%), in consonance with the usual pattern of sexual frequency during pregnancy. 1 Reduction in sexual activity at term is believed to be due to decline in sexual desire borne out of a fear of injury to the fetus, inducing labour or difficulty in finding a suitable position for coitus late in pregnancy.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Perhaps, pregnancy, by lowering vaginal pH, prohibits the growth of Gardnerella vaginalis known to thrive in alkaline medium. 11,12 Observations from our previous report on pregnancy sexuality 2 17 This study has shown that the prevalence of Gardnerella vaginalis was lower at term gestational age (12.0%) compared with pre-term (18.2%), in consonance with the usual pattern of sexual frequency during pregnancy. 1 Reduction in sexual activity at term is believed to be due to decline in sexual desire borne out of a fear of injury to the fetus, inducing labour or difficulty in finding a suitable position for coitus late in pregnancy.…”
Section: Discussionsupporting
confidence: 52%
“…This also agrees with the finding on the pattern of sexual activity during pregnancy, which similarly showed no trend in respect of social class. 2 Findings from this study unequivocally ascribe a relationship, albeit indirect, between pregnancy sexuality and the prevalence of Gardnerella vaginalis in pregnancy. This relationship needs to be corroborated by a more in-depth study involving a larger number of pregnant women.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These changes also seem to be observable in women with different parity with a notable reduction of intercourse frequency standing out in multiparous women during pregnancy in some studies [17,27], while others find that multiparous women have less orgasm problems compared to nulliparous women [28].…”
Section: Introductionmentioning
confidence: 92%